Possible interrelation between the lead time of precursory seismic electric signals (SES) and geodynamics in Aegean Sea - E. Dologlou (Natural Hazards and Earth System Sciences, 2011)
The seismicity of the last 15 years in the Aegean Sea revealed that earthquakes (Mw > 5) with epicentres falling within the Sporades basin and the confined area north of Samos island were preceded by electric seismic signals (SES) with a remarkably long lead time. A possible explanation of this behaviour by means of specific tectonics and geodynamics which characterise these two regions, such as a significant small crustal thickness and a high heat flow rate, has been attempted. New data seem to strengthen the above hypothesis.